Edukasi Pentingnya Kebersihan Diri Selama Menstruasi pada Remaja Putri di Ma’had Tahfidz Al-Quran At-Tazkiyah Cibinong Bogor - Ari Suminar; Gunarmi, Gunarmi; Hakim, Riska Ismawati (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Personal Hygiene is an action taken to maintain physical and psychological well-being through health and cleanliness. The benefits of personal hygiene during menstruation are to prevent infection, reduce odor, help stay comfortable, improve health and increase self-confidence. If you do not maintain personal hygiene during menstruation, it can cause serious health risks such as urinary tract infections, reproductive tract infections, skin irritation, infertility and other complications. This community service activity aims to increase adolescent knowledge about personal hygiene during menstruation through animated video shows accompanied by lectures at the Ma'had Tahfidz Al-Quran At-Tazkiyah Cibinong. The method used in providing health education in carrying out personal hygiene during menstruation at the Ma'had Tahfidz Al-Quran At-Tazkiyah, Cibinong District - Bogor Regency is by using animated video media and lectures which then end with a question and answer session. The results of the activity showed that before being given education, most had negative behavior as many as 49 people (70%), while after being given education, most had positive behavior as many as 52 people (74.3%), meaning that there was a change in behavioral values ​​before and after being given education. This activity successfully created an interactive atmosphere and very good enthusiasm of the participants so that it had a positive impact on awareness of personal hygiene during menstruation. This activity resulted in benefits for young women to practice personal hygiene during menstruation.